Clinical Values and Underlying Mechanism Analysis of Serum miR-455-5p in Carotid Artery Stenosis - Zhu B; Liu W; Xu Q; Liu H (Dove Medical Press, 2022)
Bin Zhu,* Wei Liu,* Qiang Xu, Hong-liang Liu Department of Neurosurgery, Renhe Hospital, Baoshan District, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Hong-liang Liu, Department of Neurosurgery, Renhe Hospital, Baoshan District, 1999 West Changjiang Road, Shanghai, 200431, People Republic of China, Tel +86-21-56731199-6083, Email Hongliang_renhe@163.comPurpose: Carotid artery stenosis (CAS) is a leading cause of cerebral infarction, its early diagnosis and intervention are necessary. In light of the important role of microRNAs (miRNAs) in cerebrovascular disease, this study aimed to investigate the expression pattern and clinical significance of serum miR-455-5p in the onset and development of CAS, as well as its underlying mechanism.Patients and Methods: Seventy patients with asymptomatic CAS were recruited, and the development of cerebral ischemia events (CIEs) was recorded during the five-years follow-up. qRT-PCR was performed for the serum miR-455-5p detection. ROC curve was applied for the diagnostic ability evaluation. By constructing multivariable logistic or cox regression model, odds ratio (OR) or hazard ratio (HR) were calculated to assess the impact of each risk factor on independent variables. Human aortic endothelial cells (HAECs) were treated with ox-LDL to induce endothelial cell damage. The role of miR-455-5p in the cell viability, apoptosis, oxidative stress and inflammatory response was detected.Results: Serum miR-455-5p showed low expression in cases with CAS, and had an independent influence on the degree of CAS. The diagnostic ability of serum miR-455-5p to diagnose CAS was determined via ROC curve, with the AUC of 0.927. During follow-up, patients with low miR-455-5p expression showed high incidence of CIEs. In multivariable cox regression model, degree of CAS and miR-455-5p were significant risk factors for the development of CIEs in the CAS patients. In vitro, miR-455-5p was at a low expression in HAECs cell models and can prevent cells from ox-LDL induced cell apoptosis, oxidative stress and inflammatory response. SOCS3 was a target gene of miR-455-5p and upregulated in ox-LDL treated cells.Conclusion: Down-regulated expression of serum miR-455-5p is hopeful to be used as a biomarker for the early diagnosis of CAS. MiR-455-5p is an independent risk factor for the degree of CAS, and has a certain predictive value for the development of CIEs. That might be associated with the protective role of miR-455-5p against ox-LDL-induced endothelial cell injury via targeting SOCS3.Keywords: microRNA-455-5p, carotid artery stenosis, cerebral ischemia events, endothelial cell injury